Bi2O3 / PTFE composite material and preparation method and hydrogen sulfide detection application thereof

Through the design of Bi2O3/PTFE composite material, the problems of slow monitoring response, high cost and poor stability of hydrogen sulfide gas in the prior art are solved, and the detection effect of high sensitivity, fast response and high stability is achieved.

CN119771339APending Publication Date: 2025-04-08DONGHUA UNIV

Patent Information

Application Number
CN202411923844.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art has problems such as slow response, high cost, complex equipment and poor stability in hydrogen sulfide gas monitoring, especially in harsh environments.

Method used

Using Bi2O3/PTFE composite material, Bi2O3 nanoparticles and PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticles are embedded in the surface and pores of PTFE nanofibers to improve the stability and binding force of the material and enhance the colorimetric sensing ability to hydrogen sulfide.

Benefits of technology

It realizes high sensitivity detection of hydrogen sulfide gas, has the advantages of fast response, high stability, low cost and strong portability, and is suitable for complex and changeable detection environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771339A_ABST
    Figure CN119771339A_ABST
Patent Text Reader

Abstract

The invention relates to a Bi2O3 / PTFE composite material and a preparation method and hydrogen sulfide detection application thereof.The Bi2O3 / PTFE composite material comprises Bi2O3 nanoparticles and PTFE nanofibers, the PTFE nanofibers are interwoven into a three-dimensional network structure, the Bi2O3 nanoparticles are distributed on the surfaces of the PTFE nanofibers and among pores of the three-dimensional network structure in a cluster mode, the Bi2O3 nanoparticles are embedded into the pores of the three-dimensional network structure, and the Bi2O3 nanoparticles are embedded into the pores of the three-dimensional network structure. The Bi2O3 nano particles are embedded on the surfaces of the PTFE nano fibers; the preparation method comprises the following steps: firstly preparing a first spinning solution and a second spinning solution, then preparing a precursor nanofiber membrane from the first spinning solution and the second spinning solution through bidirectional opposite spraying electrostatic spinning, and then sintering the precursor nanofiber membrane to obtain the product, the product is used for detecting whether hydrogen sulfide gas exists. The Bi2O3 / PTFE composite material disclosed by the invention is high in stability, and Bi2O3 nanoparticles are not easy to fall off; the preparation method is simple; the hydrogen sulfide detection is convenient, simple and portable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hazardous chemical sensors and relates to a Bi2O3 / PTFE composite material and a preparation method thereof and hydrogen sulfide detection application. Background Art

[0002] Toxic gases can cause various health problems and even threaten human life. In the fields of air quality and environmental monitoring, industrial plants, and automobile exhaust emissions, the monitoring and protection of various toxic gases are crucial. Hydrogen sulfide (H2S) is a highly toxic and irritating gas. Small amounts of H2S gas exposure can cause nasal / eye irritation, olfactory nerve paralysis, headaches, and loss of reasoning ability. Excessive concentrations can cause coma, convulsions, and even death.

[0003] In order to minimize the harm of H2S, in recent years, methods such as conductivity impedance method, potentiometric method, amperometric method, colorimetric method, absorption method, and fluorescence method have been developed to monitor the presence of H2S. For example, patent CN111735911A proposes a method for monitoring trace hydrogen sulfide gas in oil and gas devices, using a hydrogen sulfide gas sensor to collect the concentration, and then using a single-chip microcomputer to calculate the hydrogen sulfide gas concentration value. This solution may not be able to respond quickly to sudden changes in hydrogen sulfide concentration due to the gas collection and calculation process. Patent CN111912805A proposes an ultraviolet spectrum detection method for monitoring trace hydrogen sulfide in blast furnace flue gas, using ultraviolet spectrum analysis to monitor hydrogen sulfide gas, but the ultraviolet spectrum detection equipment of this solution is usually expensive and complex, and is not suitable for small-scale, portable application scenarios. Patent CN111103402A introduces a method for monitoring and controlling hydrogen sulfide in the cabin of a fishing boat, which is equipped with a complex monitoring device, display terminal, and power module, but the monitoring device of this solution is relatively complex and occupies a large space, which may not be suitable for the oil pipeline environment.

[0004] In contrast, the colorimetric method has the advantages of fast response, low cost, intuitive monitoring by naked eyes, and portability, which is conducive to large-scale promotion. The existing technology proposes to use nanoparticles and nanofiber membranes to perform colorimetric sensing of gases. Reference 1 (Mesoporous WO3 nanofibers with protein-templated nanoscale catalysts for detection of trace biomarkers in exhaled breath. ACS nano. 2016 Jun 28;10(6):5891-9.), Reference 2 (Highly selective, sensitive, and rapidly responding acetone sensor using ferroelectric ε-WO3 spheres doped with Nb for monitoring ketogenic diet efficiency. Sensors and Actuators B: Chemical. 2021 Jul 1;338:129823.) and Reference 3 (Novel templating route using Pt infiltrated block copolymer microparticles for catalytic Pt functionalized macroporous WO3 nanofibers and its application in breath pattern recognition. ACS Sensors. 2016 Sep 23;1(9):1124-31.) all use WO3 for gas sensing, but the selectivity of WO3 is poor.

[0005] Compared with WO3, Bi2O3 powder is only selective for hydrogen sulfide. The existing technology usually uses Bi2O3 powder directly for hydrogen sulfide gas sensing, or coats it on some flexible substrates (such as paper and fabric) for testing. However, these methods have the problem of uneven coating materials, and the prepared sensors are easily affected by environmental factors and cause powder to fall off, which reduces the sensor material and thus reduces the stability and sensitivity of the test.

[0006] Therefore, it is of great significance to study a Bi2O3 / PTFE composite material and its preparation method and hydrogen sulfide detection application to solve the problems existing in the prior art. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a Bi2O3 / PTFE composite material and a preparation method thereof and hydrogen sulfide detection application.

[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A Bi2O3 / PTFE composite material, the Bi2O3 / PTFE composite material comprises Bi2O3 nanoparticles and PTFE nanofibers, the PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticle clusters are distributed and embedded between the surface of the PTFE nanofibers and the pores of the three-dimensional network structure, that is, a part of the Bi2O3 nanoparticles is physically embedded in the pores of the three-dimensional network structure, and a part of the Bi2O3 nanoparticles is physically embedded on the surface of the PTFE nanofibers;

[0010] The PTFE nanofibers are interwoven into a three-dimensional network structure, which makes the porosity of the Bi2O3 / PTFE composite material high; and "a part of the Bi2O3 nanoparticles are embedded in the pores of the three-dimensional network structure, and a part of the Bi2O3 nanoparticles are physically embedded in the surface of the PTFE nanofibers" improves the binding force between the Bi2O3 nanoparticles and the PTFE nanofibers, making it difficult for the Bi2O3 nanoparticles to fall off, thereby increasing the stability of the Bi2O3 / PTFE composite material. The interwoven morphology of the PTFE nanofibers and the way in which the Bi2O3 nanoparticles are combined with the PTFE nanofibers make the Bi2O3 nanoparticles fully exposed, which is beneficial to the colorimetric sensing of hydrogen sulfide and improves the detection stability and sensitivity; among them, the cluster distribution makes the particles agglomerate larger, less likely to be wrapped, and easier to be exposed.

[0011] As the preferred technical solution:

[0012] In the Bi2O3 / PTFE composite material as described above, the Bi2O3 nanoparticles are rod-shaped Bi2O3 nanoparticles, the rod length is 5 to 10 μm, and the diameter is 500 to 800 nm. The Bi2O3 with nanorod structure is a P-type metal oxide semiconductor, and compared with other forms, it has a high specific surface area, which makes more active sites exposed to the environment. These active sites help to improve the interaction with the target molecules, thereby enhancing the sensing performance; the diameter of the PTFE nanofiber is 500 to 800 nm; the mass ratio of the Bi2O3 nanoparticles to the PTFE nanofiber is 2:1 to 10.

[0013] The Bi2O3 / PTFE composite material as described above has a porosity of 99.3% to 99.5%.

[0014] As described above, in the presence of 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite material changes from cream-yellow to brown-black within 30 seconds; Bi2O3 is a chemically stable oxide that can maintain the integrity of its chemical structure over a wide range of temperature and humidity. Even when exposed to air, it is not easy to decompose or react violently, which makes it show good stability in long-term use in gas sensors; Bi2O3 has high selectivity for hydrogen sulfide. When H2S contacts the surface of Bi2O3, colorimetric sensing occurs, and the color changes from cream yellow to brown black; Bi2O3 has good performance in a wide temperature range, and its structural stability and conductivity can also be effective at ambient temperature. Therefore, Bi2O3 / PTFE composite materials can achieve effective detection at room temperature, reducing the influence of temperature on the detection results, and further improving the service life and stability of the sensor; Bi2O3 has good stability in high humidity environments and can resist the influence of moisture to prevent the degradation of sensing performance. Humidity can have an adverse effect on some metal oxide materials, but the structure of Bi2O3 enables it to maintain stability under high humidity conditions, which helps to achieve stable H2S detection in complex environments;

[0015] The Bi2O3 / PTFE composite material of the present invention can be reused when applied to the detection of H2S gas because Bi2O3 of the Bi2O3 / PTFE composite material is converted into Bi2S3 after the detection, and Bi2S3 can be restored to the original Bi2O3 by heating at 300°C for 1 to 2 minutes.

[0016] The present invention also provides a method for preparing a Bi2O3 / PTFE composite material as described in any one of the above items, comprising mixing Bi2O3 nanoparticles, a first spinning carrier and a first solvent to obtain a first spinning solution, mixing a PTFE dispersion, a second spinning carrier and a second solvent to obtain a second spinning solution, and then subjecting the first spinning solution and the second spinning solution to bidirectional counter-spray electrospinning to obtain a precursor nanofiber membrane, and then sintering the precursor nanofiber membrane to remove the first spinning carrier and the second spinning carrier to obtain a Bi2O3 / PTFE composite material;

[0017] Spinning aid refers to auxiliary materials added to the spinning solution during the spinning process, which aims to improve the rheological properties, viscosity, surface tension, etc. of the spinning solution, thereby optimizing the formation, strength and structural stability of the fiber. PTFE has a high melting point and extremely strong chemical inertness, and is usually insoluble in conventional solvents. Electrospinning usually relies on a uniform solution, so a spinning aid (such as PEO) is required to adjust the rheological properties and viscosity of the solution so that the spinning process can proceed smoothly. The viscosity of the PTFE solution itself is usually difficult to control, and uneven fibers or breakage are prone to occur during the electrospinning process; the spinning aid can adjust the solution viscosity to a range suitable for electrospinning, which helps to form a uniform and slender fiber structure. During the electrospinning process, the spinning aid helps to improve the fiber-forming ability of PTFE and avoid breakage or instability of the solution during stretching. The molecules of the spinning aid can physically crosslink or interact with PTFE to help form a uniform fiber structure and enhance the morphology and strength of the fiber. Therefore, adding a spinning carrier to PTFE during electrospinning can effectively overcome the spinning obstacles caused by material properties, improve the structure and performance of the fiber, and thus achieve high-quality PTFE fiber formation; the reason why Bi2O3 nanoparticles require a spinning carrier is the same as above.

[0018] The decomposition temperature of the first spinning carrier and the second spinning carrier is less than the sintering temperature, the melting temperature of PTFE is less than or equal to the sintering temperature, and the decomposition temperature of PTFE is less than or equal to the sintering temperature. The melting temperature of PTFE is 330°C, the decomposition temperature is 399°C, and the sintering temperature is between the two. The Bi2O3 nanoparticles are metal oxide nanoparticles, which do not melt at the sintering temperature and do not undergo phase transformation.

[0019] The sintering time is 0.3 to 5 hours. Within this range, the spinning carrier in the Bi2O3 / PTFE / polymer composite material can be completely burned out and removed to obtain the Bi2O3 / PTFE composite material. During this time, the PTFE melts to form fibers. If this range is exceeded, the PTFE is easily melted into a block, which affects the porosity of the Bi2O3 / PTFE composite material (a decrease in porosity will result in a low exposure rate of Bi2O3).

[0020] Among them, sintering makes the Bi2O3 / PTFE composite material form a relatively large specific surface area and abundant pores, thereby providing more adsorption active sites for Bi2O3 / PTFE composite nanofibers (that is, the spinning carrier is sintered, and Bi2O3 as an active site will be exposed), which is beneficial to the colorimetric sensing of hydrogen sulfide.

[0021] Among them, PTFE comes into contact with Bi2O3 nanoparticles in a molten state, and after cooling, a good bonding effect is formed, making Bi2O3 not easy to fall off.

[0022] The present invention adopts bidirectional spray electrospinning. Figure 3 and Figure 4 From the SEM characterization, it seems that the nanoparticles prepared by the preparation method of the present invention are more fully exposed than those prepared by blending and then spinning. This is because the nanoparticles will be wrapped by the PTFE particles and the spinning carrier during blending, while the Bi2O3 / polymer composite nanofiber precursor and the PTFE / polymer composite nanofiber precursor ejected by two-way electrospinning may only be partially stacked when they meet, and one fiber precursor will not completely wrap the other fiber precursor, so that the Bi2O3 nanoparticles in the Bi2O3 / PTFE composite material will not be completely wrapped by PTFE.

[0023] As the preferred technical solution:

[0024] A method for preparing a Bi2O3 / PTFE composite material as described above, wherein the first spinning carrier and the second spinning carrier are independently selected from one or more of polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN), polyvinyl chloride (PVC) and polystyrene (PS), preferably polyethylene oxide with a molecular weight of 600,000, to ensure that the viscosity of the spinning solution is suitable for electrospinning; the first solvent and the second solvent are independently selected from one or more of deionized water, anhydrous ethanol and N, N-dimethylformamide, and when a mixed solvent is used, the precursor nanofibers obtained by electrospinning have good continuity, uniformity and surface smoothness;

[0025] The mass ratio of Bi2O3 nanoparticles, the first spinning carrier and the first solvent is 0.1-10g:0.1-1g:10g, preferably 2g:0.3g:10g; the concentration of the PTFE dispersion is 60wt%, and the ratio of the amount of PTFE dispersion, the second spinning carrier and the second solvent is 2-3mL:0.5g:9.5g, preferably 2.7mL:0.5g:9.5g.

[0026] The preparation method of the Bi2O3 / PTFE composite material as described above comprises the following specific steps:

[0027] (1) preparing a first spinning solution;

[0028] Adding Bi2O3 nanoparticles to the first solvent, performing ultrasonication for 30 minutes until completely dispersed, then adding the first spinning carrier, and stirring for 6 to 12 hours to obtain the first spinning solution;

[0029] (2) preparing a second spinning solution;

[0030] Adding the second spinning carrier into the second spinning solvent and stirring for 6 to 12 hours until the second spinning carrier is completely dissolved, and then adding the PTFE dispersion to obtain a second spinning solution;

[0031] (3) The first spinning solution and the second spinning solution are respectively loaded into syringe 1 and syringe 2, and then a precursor nanofiber membrane is obtained by bidirectional counter-jet electrospinning; wherein, the needle type used in syringe 1 and syringe 2 is 20G, that is, the inner diameter of the needle is 0.6mm, and the use of a 20G needle can obtain uniform nanofibers with a diameter of 500-800nm ​​(sintering will not affect the fiber size). If the needle is too thin, it is easy to be clogged, and if the needle is too thick, the obtained fiber is too thick, and the uniformity is reduced, which affects the performance of Bi2O3 / polymer composite nanofibers and PTFE / polymer composite nanofibers; the space between the syringe needle and the receiver is 20G. The applied voltage is 8-12 kV, preferably 8.8-9 kV. When the voltage is within the above range, the electrospinning can obtain Bi2O3 / polymer composite nanofiber precursors with uniform morphology. However, if the voltage is higher than 12 kV, it will lead to the instability of the Taylor cone, resulting in excessive stretching of the nanofibers and the breakage of the Bi2O3 / polymer composite nanofiber precursors, and the excessive electric field intensity will cause the nanofibers to have insufficient time to split and generate jets. If the voltage is lower than 8 kV, it is difficult to form a stable Taylor cone, and the Bi2O3 / polymer composite nanofiber precursors cannot be completely collected on the receiver. The voltage applied between the second needle of the emitter and the receiver is 12-13 kV, preferably 12 kV. Within the above range, the electrospinning can obtain a PTFE / polymer composite nanofiber precursor with uniform morphology. However, if the voltage is higher than 13 kV, the Taylor cone will be unstable, resulting in excessive stretching of the nanofibers and breakage of the PTFE / polymer composite nanofiber precursor. The electric field intensity is too high, resulting in insufficient time for the nanofibers to split and generate a jet. If the voltage is lower than 12 kV, it is difficult to form a stable Taylor cone, and the PTFE / polymer composite nanofiber precursor cannot be completely collected. The first syringe has a pushing speed of 2 to 2.5 mL / h, preferably 2 mL / h. If the pushing speed is within the above range, the obtained Bi2O3 / PEO composite nanofiber precursor is uniform. If the pushing speed is higher than 2.5 mL / h, liquid will accumulate at the needle tip, which may easily lead to needle clogging. If the pushing speed is lower than 2 mL / h, spinning is discontinuous and long fibers cannot be obtained. The second syringe has a pushing speed of 2 to 2.5 mL / h, preferably 2 mL / h. If the pushing speed is within the above range, the obtained PTFE / polymer composite nanofiber precursor is uniform. If the pushing speed is higher than 2.If the injection speed is lower than 5mL / h, liquid will accumulate at the needle tip, which may easily lead to needle blockage. If the injection speed is lower than 2mL / h, spinning will be discontinuous and long fibers cannot be obtained. The receiving distance of the first spinning solution is 10-15cm, and the receiving distance is the distance between the syringe and the receiver. The diameter of the Bi2O3 / polymer composite nanofiber precursor decreases with the increase of the receiving distance. If the receiving distance is greater than 15cm, the uniformity of the thickness of the cobalt oxide fiber precursor will decrease. If the receiving distance is less than 10cm, the Bi2O3 / polymer nanofiber precursor and the PTFE / polymer nanofiber precursor will stick to each other, affecting the Bi2O3 / PTFE composite. The performance of nanofibers; the receiving distance of the second spinning solution is 10-15cm; the speed of the receiver is 100-200r / min, and the spinning effect obtained by the receiver at the above speed is the most stable; the humidity of electrospinning is 30-40%, and the nanofiber precursor obtained when the humidity is higher than 40% will have many beads and will be sticky; the ambient temperature of electrospinning is 40-60℃, and the temperature higher than 40℃ is very meaningful for obtaining nanofiber precursors with controllable morphology. Increasing the ambient temperature of electrospinning can accelerate the volatilization of the solvent in the spinning solution, so that the jet solidifies quickly, thereby reducing the influence of the electric field force on the fiber diameter, and achieving the purpose of controlling the fiber diameter;.

[0032] (4) Sintering the precursor nanofiber membrane to remove the first spinning carrier and the second spinning carrier to obtain a Bi2O3 / PTFE composite material; the sintering temperature is 330-420°C. If the sintering temperature is lower than 330°C, the PTFE particles cannot be melted together, resulting in poor mechanical properties of the structurally supported PTFE fibers (PTFE is a plastic particle that cannot be adhered together without reaching the melting point. It is just that the particles are pieced together without bonding, so the mechanical properties are poor), which in turn leads to a decrease in the performance of the Bi2O3 / PTFE composite material as a hydrogen sulfide gas detector (i.e., poor mechanical properties, unable to form a membrane, and just the particles are flatly stacked together, unable to Take it up for gas detection); if the calcination temperature is higher than 420℃, it will cause PTFE to melt excessively and produce fluidity, which will lead to low porosity of Bi2O3 / PTFE composite material and reduce the gas sensitive performance of the obtained composite material; it may even carbonize PTFE and make it difficult to remove, which will damage the performance of Bi2O3 / PTFE composite material as a colorimetric sensor for hydrogen sulfide gas; the heating rate from room temperature to sintering temperature is 1-5℃ / min. If the heating rate from room temperature to sintering temperature is too fast, PTFE will shrink rapidly, which will lead to low porosity of Bi2O3 / PTFE composite material and reduce the gas sensitive performance of the obtained composite material, affecting the material performance.

[0033] According to the preparation method of a Bi2O3 / PTFE composite material as described above, after the first spinning solution and the second spinning solution are prepared, the first spinning solution and the second spinning solution are respectively defoamed by a planetary mixer, and then the first spinning solution and the second spinning solution are respectively loaded into syringe 1 and syringe 2. The defoaming treatment avoids the influence of subsequent bubbles on electrospinning. If the spinning precursor is not defoamed, the Taylor cone during electrospinning will be unstable and the collected fibers will have beads and droplets.

[0034] In the above-mentioned method for preparing a Bi2O3 / PTFE composite material, the preparation steps of Bi2O3 nanoparticles are as follows:

[0035] (1) First, Bi(NO3)3 is added to a flask, and then distilled water A is added to disperse Bi(NO3)3, and then concentrated nitric acid is added to obtain solution I, and magnetic stirring is performed until solution I is converted into a colorless, transparent, clear solution, and then distilled water B is added to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.001 to 0.01 mol / L, and finally a surfactant is added to obtain solution III; wherein the ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and surfactant is 1 to 6 g: 5 to 30 mL: 2 to 10 mL: 10 to 80 mg; the concentration of concentrated nitric acid is 16 mol / L; and the surfactant is trisodium citrate or hexadecyltrimethylammonium bromide;

[0036] (2) NaOH is added to distilled water C to prepare solution IV, and then solution IV is cooled to room temperature. Solution IV cooled to room temperature is then added dropwise to solution III to obtain solution V. Solution V gradually changes from colorless and clear to white turbidity, and then the white turbidity changes to yellow; wherein the ratio of Bi(NO3)3, NaOH and distilled water C is 1-6 g:20-60 g:200 mL;

[0037] (3) The solution V was heated at 80°C for 30 min (heating for 30 min means reacting for 30 min), then cooled to room temperature, filtered, the solid was washed with water to remove residual alkali, and then the solid was washed with ethanol to remove water, and finally dried at 60°C for 3-5 h to obtain light yellow rod-shaped Bi2O3 nanoparticles;

[0038] The preparation method of rod-shaped Bi2O3 nanoparticles is an existing technology, but the present invention has been optimized by first adding a small amount of water to disperse, then adding acid to dissolve and then diluting, which can reduce the amount of acid used. At the same time, since the alkali solution added during the reaction is excessive, the present invention collects the filtrate after the reaction, concentrates it and reuses it (five times), and it is found that the required nano-rod-shaped Bi2O3 material can still be obtained. This operation greatly reduces the amount of alkali solution used and reduces costs.

[0039] The present invention also provides an application of a Bi2O3 / PTFE composite material as described in any one of the above items, for detecting whether hydrogen sulfide gas exists.

[0040] Beneficial effects:

[0041] (1) In the Bi2O3 / PTFE composite material of the present invention, Bi2O3 nanoparticles are physically embedded on the surface of PTFE nanofibers, thereby improving the binding force between Bi2O3 nanoparticles and PTFE nanofibers, making it difficult for Bi2O3 nanoparticles to fall off, increasing the stability of the Bi2O3 / PTFE composite material, being able to maintain stable performance under long-term use and in harsh environments, and reducing the frequency of sensor replacement; the Bi2O3 / PTFE composite material can achieve high-sensitivity detection of hydrogen sulfide gas and is suitable for various complex and changeable detection environments.

[0042] (2) The Bi2O3 / PTFE composite material of the present invention has a large specific surface area, controllable fiber size, high porosity, and can provide a large number of H2S molecular adsorption sites, promote rapid diffusion and adsorption of gas, and improve sensitivity and response recovery speed. In addition, the micro-nano fiber membrane prepared by electrospinning technology can be directly sewn, embroidered, or even woven into clothing, which is conducive to portable monitoring of H2S gas.

[0043] (3) The method for preparing a Bi2O3 / PTFE composite material of the present invention adopts a film prepared by bidirectional opposite-direction spray spinning, which can better fix Bi2O3 on the film through PTFE, thereby improving the stability of the material.

[0044] (4) The application of a Bi2O3 / PTFE composite material of the present invention combines the visual detection of color changes with a portable design, making the detection process more intuitive and simple, and users can obtain accurate results without complex equipment; it has significant advantages in portability and user-friendliness, and can provide efficient and reliable gas monitoring solutions in various industrial and civil fields.

[0045] (5) The application of a Bi2O3 / PTFE composite material of the present invention combines visual detection with safe and environmentally friendly materials, providing a more intuitive and non-toxic detection solution than traditional lead acetate, and excels in improving selectivity and anti-interference, effectively reducing the influence of other gases and moisture on the detection results, and significantly reducing the false alarm rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 is a SEM image of the Bi2O3 nanorods of Example 1;

[0047] Figure 2is the XRD image of the Bi2O3 nanorods of Example 1;

[0048] Figure 3 is a SEM image of the Bi2O3 / PTFE composite material prepared in Example 1;

[0049] Figure 4 This is the SEM image of the fiber membrane produced by the existing blending electrospinning technology. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0051] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:

[0052] (1) Porosity: The porosity test was performed using McMerritt ASAP 2020 V4.00.

[0053] (2) Colorimetric sensing response of Bi2O3 / PTFE composite material to 10ppm hydrogen sulfide gas: A hydrogen sulfide gas testing platform was used to detect the presence of hydrogen sulfide gas;

[0054] The hydrogen sulfide gas testing platform includes a closed gas chamber, a controllable hydrogen sulfide gas inlet, a hydrogen sulfide gas concentration detector and a camera for recording; a hydrogen sulfide gas valve and a hydrogen sulfide gas concentration detector are installed in the closed gas chamber; the hydrogen sulfide gas concentration is adjusted by the hydrogen sulfide gas valve, and the hydrogen sulfide gas concentration detector can detect the hydrogen sulfide gas concentration in real time;

[0055] The reaction time of the colorimetric gas sensing device in hydrogen sulfide gas is controlled, and the reaction is recorded with a camera. The colorimetric sensing element after the reaction (ie, the Bi2O3 / PTFE composite material) is then compared with the unreacted colorimetric sensing element to compare their color changes.

[0056] The specific test process is as follows: the Bi2O3 / PTFE composite material is placed in a glove box (i.e., a closed gas chamber), and then hydrogen sulfide gas is introduced into the glove box to ensure that the hydrogen sulfide gas in the glove box reaches saturated vapor (10ppm). The Bi2O3 / PTFE composite material is reacted in a 10ppm environment for 30s, 60s, and 120s, and the color change is recorded by a camera. The color change is compared with the composite material that has not been in contact with hydrogen sulfide gas to test its colorimetric sensing performance.

[0057] The information of some substances of the present invention is as follows:

[0058] PTFE dispersion: ALADDIN, 60 wt% dispersion.

[0059] Trisodium citrate: MACKLIN / McKlin, ≥99% (GC).

[0060] NaOH: AR (Shanghai test), flake.

[0061] Anhydrous ethanol: AR (Shanghai test), ≥99.7%.

[0062] Polyethylene oxide: Mw is 600,000.

[0063] Polyvinyl alcohol: Manufacturer: Sane Chemical Technology (Shanghai) Co., Ltd., brand: 9002-89-5, Mw ~ 50,000.

[0064] Polyvinylpyrrolidone: Manufacturer: Sane Chemical Technology (Shanghai) Co., Ltd., brand: 9003-39-8, Mw ~ 300,000.

[0065] Polyacrylonitrile: Manufacturer: MACKLIN, Brand: 25014-41-9, Mw~350,000.

[0066] Polyvinyl chloride: Manufacturer: MACKLIN, Mw~350,000.

[0067] Polystyrene: Mw ~ 192,000.

[0068] Example 1

[0069] A method for preparing a Bi2O3 / PTFE composite material, the specific steps are as follows:

[0070] (1) The preparation steps of Bi2O3 nanoparticles are as follows:

[0071] (1.1) First, add Bi(NO3)3 into a flask, then add distilled water A to disperse the Bi(NO3)3, then add concentrated nitric acid with a concentration of 16 mol / L to obtain solution I, stir magnetically until solution I is converted into a colorless, transparent, clear solution, then add distilled water B to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.001 mol / L, and finally add trisodium citrate to obtain solution III; wherein the ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and trisodium citrate is 1 g:30 mL:2 mL:10 mg;

[0072] (1.2) NaOH was added to distilled water C to prepare solution IV, and then solution IV was cooled to room temperature, and then solution IV cooled to room temperature was added dropwise to solution III at a rate of 0.05 mL / s to obtain solution V; wherein the ratio of Bi(NO3)3, NaOH and distilled water C was 1 g:20 g:200 mL;

[0073] (1.3) Solution V was heated at 80°C for 30 min, then cooled to room temperature, filtered, the solid was washed with water to remove residual alkali, and then the solid was washed with ethanol to remove water, and finally dried at 60°C for 3 h to obtain rod-shaped Bi2O3 nanoparticles with a rod length of 5 to 10 μm and a diameter of 500 to 800 nm;

[0074] (2) preparing a first spinning solution;

[0075] The Bi2O3 nanoparticles were added to a mixed solvent of N,N-dimethylformamide and deionized water in a mass ratio of 3:7, and ultrasonicated for 30 minutes until they were completely dispersed, and then polyethylene oxide was added, and heated and stirred at a water bath temperature of 90° C. for 6 hours to obtain a first spinning solution;

[0076] The mass ratio of Bi2O3 nanoparticles, polyethylene oxide, and a mixed solvent of N,N-dimethylformamide and deionized water in a mass ratio of 3:7 is 0.1 g: 0.1 g: 10 g;

[0077] (3) preparing a second spinning solution;

[0078] Adding polyethylene oxide to a mixed solvent of N,N-dimethylformamide and deionized water in a mass ratio of 3:7 and stirring for 6 hours until the polyethylene oxide is completely dissolved, and then adding a 60 wt % PTFE dispersion to obtain a second spinning solution;

[0079] The ratio of the amount of PTFE dispersion, polyethylene oxide, and a mixed solvent of N,N-dimethylformamide and deionized water in a mass ratio of 3:7 is 2 mL: 0.5 g: 9.5 g;

[0080] (4) defoaming the first spinning solution prepared in step (2) and the second spinning solution prepared in step (3) for 30 minutes using a planetary mixer;

[0081] (5) The first spinning solution and the second spinning solution after defoaming treatment are respectively loaded into syringe one and syringe two, and then a precursor nanofiber membrane is obtained by bidirectional spray electrospinning; wherein, the needles used in syringe one and syringe two are of 20G type, the voltage applied between the needle of syringe one and the receiver is 8kV, the voltage applied between the needle of syringe two and the receiver is 12kV, the propulsion speed of syringe one is 2mL / h, the propulsion speed of syringe two is 2mL / h, the receiving distance of the first spinning solution is 10cm, and the receiving distance of the second spinning solution is 12cm; the rotation speed of the receiver is 150r / min; the humidity of electrospinning is 40%; the ambient temperature of electrospinning is 40°C;

[0082] (6) The temperature was raised to 350°C at a heating rate of 1°C / min at room temperature, and the precursor nanofiber membrane was sintered for 0.5 h to remove the first spinning support and the second spinning support to obtain a Bi2O3 / PTFE composite material.

[0083] like Figure 3 As shown, the final Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers, the diameter of the PTFE nanofibers is 500-800nm; the mass ratio of Bi2O3 nanoparticles to PTFE nanofibers is 1:12; the PTFE nanofibers are interwoven into a three-dimensional network structure, and the Bi2O3 nanoparticle clusters are distributed and embedded in the surface of the PTFE nanofibers and the pores of the three-dimensional network structure; the Bi2O3 / PTFE composite material is in the form of a film, with a length of 40cm and a width of 35cm; the porosity of the Bi2O3 / PTFE composite material is 99.3%.

[0084] Bi2O3 / PTFE composite materials are used to detect the presence of hydrogen sulfide gas; under 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite materials change from cream yellow to brown black within 30 seconds.

[0085] like Figure 1 The SEM image shown shows that the Bi2O3 nanorods are rod-like structures;

[0086] like Figure 2 The XRD pattern shown shows that Bi2O3 is α phase.

[0087] Example 2

[0088] A method for preparing a Bi2O3 / PTFE composite material is basically the same as Example 1, except that trisodium citrate in step (1.1) is replaced by cetyltrimethylammonium bromide (CTAB).

[0089] The final Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers, the diameter of the PTFE nanofibers is 500-800nm; the mass ratio of Bi2O3 nanoparticles to PTFE nanofibers is 1:12; the PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticle clusters are distributed and embedded in the surface of the PTFE nanofibers and the pores of the three-dimensional network structure; the Bi2O3 / PTFE composite material is in the form of a film, with a length of 40cm and a width of 35cm; the porosity of the Bi2O3 / PTFE composite material is 99.3%.

[0090] Example 3

[0091] A method for preparing a Bi2O3 / PTFE composite material, the specific steps are as follows:

[0092] (1) The preparation steps of Bi2O3 nanoparticles are as follows:

[0093] (1.1) First, add Bi(NO3)3 into a flask, then add distilled water A to disperse the Bi(NO3)3, then add concentrated nitric acid with a concentration of 16 mol / L to obtain solution I, stir magnetically until solution I is converted into a colorless, transparent, clear solution, then add distilled water B to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.003 mol / L, and finally add trisodium citrate to obtain solution III; wherein the ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and trisodium citrate is 2 g:30 mL:4 mL:20 mg;

[0094] (1.2) NaOH was added to distilled water C to prepare solution IV, and then solution IV was cooled to room temperature, and then solution IV cooled to room temperature was added dropwise to solution III at a rate of 0.05 mL / s to obtain solution V; wherein the ratio of Bi(NO3)3, NaOH and distilled water C was 2 g:30 g:200 mL;

[0095] (1.3) Solution V was heated at 80°C for 30 min, then cooled to room temperature, filtered, the solid was washed with water to remove residual alkali, and then the solid was washed with ethanol to remove water, and finally dried at 60°C for 4 h to obtain rod-shaped Bi2O3 nanoparticles with a rod length of 5 to 10 μm and a diameter of 500 to 800 nm;

[0096] (2) preparing a first spinning solution;

[0097] The Bi2O3 nanoparticles were added to anhydrous ethanol, ultrasonicated for 30 minutes until completely dispersed, and then polyvinyl alcohol was added, and heated and stirred at a water bath temperature of 90°C for 8 hours to obtain a first spinning solution;

[0098] Among them, the mass ratio of Bi2O3 nanoparticles, polyvinyl alcohol and anhydrous ethanol is 2g:0.3g:10g;

[0099] (3) preparing a second spinning solution;

[0100] Add polyvinyl alcohol to anhydrous ethanol and stir for 8 hours until the polyvinyl alcohol is completely dissolved, and then add 60 wt% PTFE dispersion to prepare a second spinning solution;

[0101] The ratio of PTFE dispersion, polyvinyl alcohol and anhydrous ethanol is 2.5 mL: 0.5 g: 9.5 g;

[0102] (4) defoaming the first spinning solution prepared in step (2) and the second spinning solution prepared in step (3) for 30 minutes using a planetary mixer;

[0103] (5) The first spinning solution and the second spinning solution after defoaming treatment are respectively loaded into syringe one and syringe two, and then a precursor nanofiber membrane is obtained by bidirectional spray electrospinning; wherein, the needle model used in syringe one and syringe two is 20G, the voltage applied between the needle of syringe one and the receiver is 9kV, the voltage applied between the needle of syringe two and the receiver is 12.2kV, the propulsion speed of syringe one is 2.1mL / h, the propulsion speed of syringe two is 2.1mL / h, the receiving distance of the first spinning solution is 11cm, and the receiving distance of the second spinning solution is 11cm; the rotation speed of the receiver is 120r / min; the humidity of electrospinning is 38%; the ambient temperature of electrospinning is 45°C;

[0104] (6) The temperature was raised to 350°C at a heating rate of 2°C / min at room temperature, and the precursor nanofiber membrane was sintered for 4 h to remove the first spinning support and the second spinning support to obtain a Bi2O3 / PTFE composite material.

[0105] The final Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers, the diameter of the PTFE nanofibers is 500-800nm; the mass ratio of Bi2O3 nanoparticles to PTFE nanofibers is 4:3; the PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticle clusters are distributed and embedded in the surface of the PTFE nanofibers and the pores of the three-dimensional network structure; the Bi2O3 / PTFE composite material is in the form of a film, with a length of 40cm and a width of 35cm; the porosity of the Bi2O3 / PTFE composite material is 99.4%.

[0106] Bi2O3 / PTFE composite materials are used to detect the presence of hydrogen sulfide gas; under 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite materials change from cream yellow to brown black within 30 seconds.

[0107] Example 4

[0108] A method for preparing a Bi2O3 / PTFE composite material, the specific steps are as follows:

[0109] (1) The preparation steps of Bi2O3 nanoparticles are as follows:

[0110] (1.1) First, add Bi(NO3)3 into a flask, then add distilled water A to disperse the Bi(NO3)3, then add concentrated nitric acid with a concentration of 16 mol / L to obtain solution I, stir magnetically until solution I is converted into a colorless, transparent, clear solution, then add distilled water B to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.005 mol / L, and finally add trisodium citrate to obtain solution III; wherein the ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and trisodium citrate is 3 g:20 mL:6 mL:30 mg;

[0111] (1.2) NaOH was added to distilled water C to prepare solution IV, and then solution IV was cooled to room temperature, and then solution IV cooled to room temperature was added dropwise to solution III at a rate of 0.05 mL / s to obtain solution V; wherein the ratio of Bi(NO3)3, NaOH and distilled water C was 3 g:40 g:200 mL;

[0112] (1.3) Solution V was heated at 80°C for 30 min, then cooled to room temperature, filtered, the solid was washed with water to remove residual alkali, and then the solid was washed with ethanol to remove water, and finally dried at 60°C for 5 h to obtain rod-shaped Bi2O3 nanoparticles with a rod length of 5 to 10 μm and a diameter of 500 to 800 nm;

[0113] (2) preparing a first spinning solution;

[0114] The Bi2O3 nanoparticles were added to N,N-dimethylformamide, ultrasonicated for 30 minutes until completely dispersed, and then polyvinyl pyrrolidone was added, and heated and stirred at a water bath temperature of 90°C for 10 hours to obtain a first spinning solution;

[0115] Wherein, the mass ratio of Bi2O3 nanoparticles, polyvinyl pyrrolidone and N,N-dimethylformamide is 3g:0.3g:10g;

[0116] (3) preparing a second spinning solution;

[0117] Add polyacrylonitrile to N,N-dimethylformamide and stir for 9 hours until the polyacrylonitrile is completely dissolved, and then add 60 wt% PTFE dispersion to obtain a second spinning solution;

[0118] The ratio of PTFE dispersion, polyacrylonitrile and N,N-dimethylformamide is 2.5mL:0.5g:9.5g;

[0119] (4) defoaming the first spinning solution prepared in step (2) and the second spinning solution prepared in step (3) for 30 minutes using a planetary mixer;

[0120] (5) The first spinning solution and the second spinning solution after defoaming treatment are respectively loaded into syringe one and syringe two, and then a precursor nanofiber membrane is obtained by bidirectional counter-jet electrospinning; wherein, the needles used in syringe one and syringe two are of 20G type, the voltage applied between the needle of syringe one and the receiver is 11kV, the voltage applied between the needle of syringe two and the receiver is 12.5kV, the propulsion speed of syringe one is 2.2mL / h, the propulsion speed of syringe two is 2.2mL / h, the receiving distance of the first spinning solution is 15cm, and the receiving distance of the second spinning solution is 12cm; the rotation speed of the receiver is 150r / min; the humidity of electrospinning is 35%; the ambient temperature of electrospinning is 50℃;

[0121] (6) heating the temperature to 385° C. at a heating rate of 3° C. / min at room temperature, and then sintering the precursor nanofiber membrane for 3 h to remove the first spinning support and the second spinning support to obtain a Bi2O3 / PTFE composite material;

[0122] The final Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers, the diameter of the PTFE nanofibers is 500-800nm; the mass ratio of Bi2O3 nanoparticles to PTFE nanofibers is 2:1; the PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticle clusters are distributed and embedded in the surface of the PTFE nanofibers and the pores of the three-dimensional network structure; the Bi2O3 / PTFE composite material is in the form of a film, with a length of 40cm and a width of 35cm; the porosity of the Bi2O3 / PTFE composite material is 99.5%.

[0123] Bi2O3 / PTFE composite materials are used to detect the presence of hydrogen sulfide gas; under 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite materials change from cream yellow to brown black within 30 seconds.

[0124] Example 5

[0125] A method for preparing a Bi2O3 / PTFE composite material, the specific steps are as follows:

[0126] (1) The preparation steps of Bi2O3 nanoparticles are as follows:

[0127] (1.1) First, add Bi(NO3)3 into a flask, then add distilled water A to disperse Bi(NO3)3, then add concentrated nitric acid with a concentration of 16 mol / L to obtain solution I, stir magnetically until solution I is converted into a colorless, transparent, clear solution, then add distilled water B to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.008 mol / L, and finally add trisodium citrate to obtain solution III; wherein the ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and trisodium citrate is 4.5 g:30 mL:8 mL:60 mg;

[0128] (1.2) NaOH was added to distilled water C to prepare solution IV, and then solution IV was cooled to room temperature, and then solution IV cooled to room temperature was added dropwise to solution III at a rate of 0.1 mL / s to obtain solution V; wherein the ratio of Bi(NO3)3, NaOH and distilled water C was 4.5 g:40 g:200 mL;

[0129] (1.3) Solution V was heated at 80°C for 30 min, then cooled to room temperature, filtered, the solid was washed with water to remove residual alkali, and then the solid was washed with ethanol to remove water, and finally dried at 60°C for 3.5 h to obtain rod-shaped Bi2O3 nanoparticles with a rod length of 5 to 10 μm and a diameter of 500 to 800 nm;

[0130] (2) preparing a first spinning solution;

[0131] The Bi2O3 nanoparticles were added to deionized water, ultrasonicated for 30 minutes until completely dispersed, and then polyacrylonitrile was added, and heated and stirred at a water bath temperature of 90°C for 12 hours to obtain a first spinning solution;

[0132] Among them, the mass ratio of Bi2O3 nanoparticles, polyacrylonitrile and deionized water is 6g:0.4g:10g;

[0133] (3) preparing a second spinning solution;

[0134] Add polyvinyl pyrrolidone to anhydrous ethanol and stir for 10 hours until the polyvinyl pyrrolidone is completely dissolved, and then add 60 wt% PTFE dispersion to prepare a second spinning solution;

[0135] The ratio of PTFE dispersion, polyvinyl pyrrolidone and anhydrous ethanol is 2.5 mL: 0.5 g: 9.5 g;

[0136] (4) defoaming the first spinning solution prepared in step (2) and the second spinning solution prepared in step (3) for 30 minutes using a planetary mixer;

[0137] (5) The first spinning solution and the second spinning solution after defoaming treatment are respectively loaded into syringe one and syringe two, and then a precursor nanofiber membrane is obtained by bidirectional spray electrospinning; wherein, the needles used in syringe one and syringe two are of 20G, the voltage applied between the needle of syringe one and the receiver is 10kV, the voltage applied between the needle of syringe two and the receiver is 12.8kV, the propulsion speed of syringe one is 2.3mL / h, the propulsion speed of syringe two is 2.4mL / h, the receiving distance of the first spinning solution is 13cm, and the receiving distance of the second spinning solution is 14cm; the rotation speed of the receiver is 180r / min; the humidity of electrospinning is 32%; the ambient temperature of electrospinning is 55°C;

[0138] (6) heating the temperature to 400° C. at a heating rate of 4° C. / min at room temperature, and then sintering the precursor nanofiber membrane for 1 h to remove the first spinning support and the second spinning support to obtain a Bi2O3 / PTFE composite material;

[0139] The final Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers, the diameter of the PTFE nanofibers is 500-800nm; the mass ratio of Bi2O3 nanoparticles to PTFE nanofibers is 4:1; the PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticle clusters are distributed and embedded in the surface of the PTFE nanofibers and the pores of the three-dimensional network structure; the Bi2O3 / PTFE composite material is in the form of a film, with a length of 40cm and a width of 35cm; the porosity of the Bi2O3 / PTFE composite material is 99.3%.

[0140] Bi2O3 / PTFE composite materials are used to detect the presence of hydrogen sulfide gas; under 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite materials change from cream yellow to brown black within 30 seconds.

[0141] Example 6

[0142] A method for preparing a Bi2O3 / PTFE composite material, the specific steps are as follows:

[0143] (1) The preparation steps of Bi2O3 nanoparticles are as follows:

[0144] (1.1) First, add Bi(NO3)3 into a flask, then add distilled water A to disperse the Bi(NO3)3, then add concentrated nitric acid with a concentration of 16 mol / L to obtain solution I, stir magnetically until solution I is converted into a colorless, transparent, clear solution, then add distilled water B to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.01 mol / L, and finally add trisodium citrate to obtain solution III; wherein the ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and trisodium citrate is 6 g:10 mL:10 mL:80 mg;

[0145] (1.2) NaOH was added to distilled water C to prepare solution IV, and then solution IV was cooled to room temperature, and then solution IV cooled to room temperature was added dropwise to solution III at a rate of 0.1 mL / s to obtain solution V; wherein the ratio of Bi(NO3)3, NaOH and distilled water C was 6 g:60 g:200 mL;

[0146] (1.3) Solution V was heated at 80°C for 30 min, then cooled to room temperature, filtered, and the solid was washed with water to remove residual alkali, and then washed with ethanol to remove water, and finally dried at 60°C for 4.5 h to obtain rod-shaped Bi2O3 nanoparticles with a rod length of 5 to 10 μm and a diameter of 500 to 800 nm;

[0147] (2) preparing a first spinning solution;

[0148] The Bi2O3 nanoparticles were added to a mixed solvent of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:1, and ultrasonicated for 30 minutes until completely dispersed, and then a mixture of polyvinyl chloride and polystyrene in a mass ratio of 1:1 was added, and heated and stirred at a water bath temperature of 90°C for 9 hours to obtain a first spinning solution;

[0149] The mass ratio of Bi2O3 nanoparticles, a mixture of polyvinyl chloride and polystyrene in a mass ratio of 1:1, and a mixed solvent of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:1 is 10g:1g:10g;

[0150] (3) preparing a second spinning solution;

[0151] A mixture of polyvinyl chloride and polystyrene in a mass ratio of 1:1 is added to a mixed solvent of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:1, and stirred for 12 hours until the mixture of polyvinyl chloride and polystyrene in a mass ratio of 1:1 is completely dissolved, and then a PTFE dispersion with a concentration of 60wt% is added to obtain a second spinning solution;

[0152] The ratio of the amount of PTFE dispersion, the mixture of polyvinyl chloride and polystyrene in a mass ratio of 1:1, and the mixed solvent of anhydrous ethanol and N,N-dimethylformamide in a volume ratio of 1:1 is 3 mL: 0.5 g: 9.5 g;

[0153] (4) defoaming the first spinning solution prepared in step (2) and the second spinning solution prepared in step (3) for 30 minutes using a planetary mixer;

[0154] (5) The first spinning solution and the second spinning solution after defoaming treatment are respectively loaded into syringe one and syringe two, and then a precursor nanofiber membrane is obtained by bidirectional spray electrospinning; wherein, the model of the needle used in syringe one and syringe two is 20G, the voltage applied between the needle of syringe one and the receiver is 12kV, the voltage applied between the needle of syringe two and the receiver is 13kV, the propulsion speed of syringe one is 2.5mL / h, the propulsion speed of syringe two is 2.5mL / h, the receiving distance of the first spinning solution is 15cm, and the receiving distance of the second spinning solution is 15cm; the rotation speed of the receiver is 200r / min; the humidity of electrospinning is 30%; the ambient temperature of electrospinning is 60℃;

[0155] (6) heating the temperature to 420° C. at a heating rate of 5° C. / min at room temperature, and then sintering the precursor nanofiber membrane for 0.5 h to remove the first spinning support and the second spinning support to obtain a Bi2O3 / PTFE composite material;

[0156] The final Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers, the diameter of the PTFE nanofibers is 500-800nm; the mass ratio of Bi2O3 nanoparticles to PTFE nanofibers is 20:3; the PTFE nanofibers are interwoven into a three-dimensional network structure, and Bi2O3 nanoparticle clusters are distributed and embedded in the surface of the PTFE nanofibers and the pores of the three-dimensional network structure; the Bi2O3 / PTFE composite material is in the form of a film, with a length of 40cm and a width of 35cm; the porosity of the Bi2O3 / PTFE composite material is 99.45%.

[0157] Bi2O3 / PTFE composite materials are used to detect the presence of hydrogen sulfide gas; under 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite materials change from cream yellow to brown black within 30 seconds.

Claims

1. A Bi2O3 / PTFE composite material, characterized in that: The Bi2O3 / PTFE composite material includes Bi2O3 nanoparticles and PTFE nanofibers. The PTFE nanofibers are interwoven into a three-dimensional network structure. The Bi2O3 nanoparticle clusters are distributed and embedded on the surface of the PTFE nanofibers and between the pores of the three-dimensional network structure.

2. A Bi2O3 / PTFE composite material according to claim 1, characterized in that: The Bi2O3 nanoparticles are rod-shaped Bi2O3 nanoparticles with a rod length of 5 to 10 μm and a diameter of 500 to 800 nm; the diameter of the PTFE nanofibers is 500 to 800 nm; and the mass ratio of the Bi2O3 nanoparticles to the PTFE nanofibers is 2:1 to 10.

3. A Bi2O3 / PTFE composite material according to claim 2, characterized in that: The porosity of the Bi2O3 / PTFE composite material is 99.3% to 99.5%.

4. A Bi2O3 / PTFE composite material according to claim 3, characterized in that: Under 10 ppm hydrogen sulfide gas, the Bi2O3 / PTFE composite material changes from cream yellow to brown black within 30 s.

5. A method for preparing a Bi2O3 / PTFE composite material according to any one of claims 1 to 4, characterized in that: The Bi2O3 nanoparticles, the first spinning carrier and the first solvent are mixed to obtain a first spinning solution, the PTFE dispersion, the second spinning carrier and the second solvent are mixed to obtain a second spinning solution, and then the first spinning solution and the second spinning solution are subjected to bidirectional counter-spray electrospinning to obtain a precursor nanofiber membrane, and then the precursor nanofiber membrane is sintered to remove the first spinning carrier and the second spinning carrier to obtain a Bi2O3 / PTFE composite material; The decomposition temperature of the first spinning carrier and the second spinning carrier is less than the sintering temperature, the melting temperature of PTFE is less than or equal to the sintering temperature, and the decomposition temperature of PTFE; the sintering time is 0.3 to 5 hours.

6. The method for preparing a Bi2O3 / PTFE composite material according to claim 5, characterized in that: The first spinning carrier and the second spinning carrier are each independently selected from at least one of polyethylene oxide, polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylonitrile, polyvinyl chloride and polystyrene; the first solvent and the second solvent are each independently selected from at least one of deionized water, anhydrous ethanol and N,N-dimethylformamide; The mass ratio of Bi2O3 nanoparticles, the first spinning carrier and the first solvent is 0.1-10g:0.1-1g:10g; the concentration of PTFE dispersion is 60wt%, and the usage ratio of PTFE dispersion, the second spinning carrier and the second solvent is 2-3mL:0.5g:9.5g.

7. The method for preparing a Bi2O3 / PTFE composite material according to claim 5, characterized in that: The specific steps are as follows: (1) preparing a first spinning solution; Adding Bi2O3 nanoparticles to the first solvent, performing ultrasonication for 30 minutes until completely dispersed, then adding the first spinning carrier, and stirring for 6 to 12 hours to obtain the first spinning solution; (2) preparing a second spinning solution; Adding the second spinning carrier into the second spinning solvent and stirring for 6 to 12 hours until the second spinning carrier is completely dissolved, and then adding the PTFE dispersion to obtain a second spinning solution; (3) The first spinning solution and the second spinning solution are respectively loaded into syringe one and syringe two, and then a precursor nanofiber membrane is obtained by bidirectional spray electrospinning; wherein the needles used in syringe one and syringe two are of 20G; the voltage applied between the needle of syringe one and the receiver is 8-12 kV; the voltage applied between the needle of syringe two and the receiver is 12-13 kV; the propulsion speed of syringe one is 2-2.5 mL / h; the propulsion speed of syringe two is 2-2.5 mL / h; the receiving distance of the first spinning solution is 10-15 cm; the receiving distance of the second spinning solution is 10-15 cm; the rotation speed of the receiver is 100-200 r / min; the humidity of electrospinning is 30-40%; the ambient temperature of electrospinning is 40-60°C; (4) Sintering the precursor nanofiber membrane to remove the first spinning carrier and the second spinning carrier to obtain a Bi2O3 / PTFE composite material; the sintering temperature is 330-420°C; and the heating rate from room temperature to the sintering temperature is 1-5°C / min.

8. The method for preparing a Bi2O3 / PTFE composite material according to claim 7, characterized in that: After the first spinning solution and the second spinning solution are prepared, the first spinning solution and the second spinning solution are respectively subjected to defoaming treatment by a planetary mixer.

9. The method for preparing a Bi2O3 / PTFE composite material according to claim 8, characterized in that: The preparation steps of Bi2O3 nanoparticles are as follows: (1) First, Bi(NO3)3 is added to a flask, and then distilled water A is added to disperse the Bi(NO3)3, and then concentrated nitric acid is added to obtain solution I, and magnetic stirring is performed until solution I is converted into a colorless, transparent, clear solution, and then distilled water B is added to dilute the colorless, transparent, clear solution to obtain solution II with a Bi(NO3)3 concentration of 0.001 to 0.01 mol / L, and finally a surfactant is added to obtain solution III; The ratio of Bi(NO3)3, distilled water A, concentrated nitric acid and surfactant is 1-6g:5-30mL:2-10mL:10-80mg; the concentration of concentrated nitric acid is 16mol / L; the surfactant is trisodium citrate or hexadecyltrimethylammonium bromide; (2) NaOH is added to distilled water C to prepare solution IV, and then solution IV is cooled to room temperature, and then solution IV cooled to room temperature is added dropwise to solution III to obtain solution V; wherein the ratio of Bi(NO3)3, NaOH and distilled water C is 1-6 g:20-60 g:200 mL; (3) The solution V was heated at 80°C for 30 min to obtain Bi2O3 nanoparticles.

10. Use of a Bi2O3 / PTFE composite material according to any one of claims 1 to 4, characterized in that: Used to detect the presence of hydrogen sulfide gas.

Citation Information

Patent Citations

  • Fishing boat cabin hydrogen sulfide monitoring and control method

    CN111103402A

  • Ultraviolet spectrum detection method and device for monitoring trace hydrogen sulfide in blast furnace flue gas

    CN111912805A

Cited By

  • H2S sensing device for monitoring freshness of agricultural products and preparation method of H2S sensing device

    CN121113998A